Development of Mg–Al–La tri-metal mixed oxide entrapped in alginate for removal of fluoride from wastewater. Issue 50 (16th June 2017) - Wang, Aihe; Zhou, Kanggen; Liu, Xing; Liu, Fang; Chen, Quanzhou
Abstract : New biopolymer beads, composite of Mg–AL–La tri-metal oxides and alginate, were synthesized, characterized and tested for their fluoride removal efficiency from wastewater. The maximum adsorption capacity of the adsorbent was 30.9 mg g −1 . Abstract : New biopolymer beads, composed of a Mg–Al–La tri-metal oxide (MAL) and alginate (SA), were synthesized, characterized and tested for their fluoride removal efficiency from wastewater. The morphology and properties of the beads were characterized by Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). Batch sorption studies were carried out to investigate the adsorption capacity of fluoride on SA-CMAL. The equilibrium sorption data were analyzed using the adsorption isotherm models of Langmuir and Freundlich. To explore the adsorption mechanism, thermodynamic parameters including Δ H 0, Δ S 0 and Δ G 0 were calculated from the results of adsorption thermodynamics. The maximum adsorption capacity of fluoride adsorption on SA-CMAL was 30.96 mg g −1 at 303 K. Compared with the Langmuir model, the Freundlich isotherm model better fitted the equilibrium data. In addition, the adsorption process was best fitted with pseudo-second-order kinetics. The value of the thermodynamic parameter Δ H 0 indicated an exothermic adsorption process. A negative value of Δ G 0 shows the feasibility and spontaneity of material–anion interaction. The detrimental effect of co-existing anions increased in the order SO4 2− < NO3 − < CO3 2− < PO4 2− .